STUDENTS’ ENGLISH SUMMATIVE TEST ANALYSIS: A CASE STUDY AT SMA PERGURUAN RAKYAT 1 JAKARTA - Siti Nurani; Mulyadi Mulyadi (Scope : Journal of English Language Teaching, 2020)
The present research aims at analyzing the English summative test at SMA Perguruan Rakyat 1 in the Second Term of 2018/2019 Academic Year. The analysis concerns to difficulty level and discriminating power to know the teacher-made test English summative test at SMA Perguruan Rakyat 1 whether or not the test has good items, especially of its difficulty level, discriminating power and the effectiveness of the distracters. Such research procedures are employed, such as observation, literature review and statistical analysis. Specifically, the result of the research is expected to be beneficial for educational practitioners to have a more-depth insight of English summative test analysis. Furthermore, the result of the research is also expected to give valuable knowledge for those who are interested in analyzing the English summative test writing, mainly to the indicators of its discriminating power and distracters. Lastly, it is also hoped to be as reference for further researchers to draw related concepts of English summative test analysis that is integrated with various disciplines implemented in the classroom contexts.